Ablation and antiarrhythmic drug effects on PITX2+/− deficient atrial fibrillation: A computational modeling study - Jin, Ze; Hwang, Inseok; Lim, Byounghyun; Kwon, Oh-Seok; Park, Je-Wook; Yu, Hee-Tae; Kim, Tae-Hoon; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Atrial fibrillation (AF) is a heritable disease, and the paired-like homeodomain transcription factor 2 (PITX2) gene is highly associated with AF. We explored the differences in the circumferential pulmonary vein isolation (CPVI), which is the corner stone procedure for AF catheter ablation, additional high dominant frequency (DF) site ablation, and antiarrhythmic drug (AAD) effects according to the patient genotype (wild type and PITX2+/- deficient) using computational modeling. Methods: We included 25 AF patients (68% male, 59.8±9.8 years of age, 32.0% paroxysmal AF) who underwent AF catheter ablation to develop a realistic computational AF model. The ion currents for baseline AF and the amiodarone, dronedarone, and flecainide AADs according to the patient genotype (wild type and PITX2+/- deficient) were defined by relevant publications. We tested the virtual CPVI (V-CPVI) with and without DF ablation (DFA) and three virtual AADs (V-AADs, amiodarone, dronedarone, and flecainide) and evaluated the AF defragmentation rates (AF termination or changes to regular atrial tachycardia (AT), DF, and maximal slope of the action potential duration restitution curves (Smax), which indicates the vulnerability of wave-breaks. Results: At the baseline AF, mean DF (p=0.003), and Smax (p<0.001) were significantly lower in PITX2+/- deficient patients than wild-type patients. In the overall AF episodes, V-CPVI (DFA) resulted in a higher AF defragmentation relative to V-AADs (65.0% vs. 42.0%, p<0.001) without changing the DF or Smax. Although a PITX2+/- deficiency did not affect the AF defragmentation rate after the V-CPVI (DFA), V-AADs had a higher AF defragmentation rate (p=0.014), lower DF (p<0.001), and lower Smax (p=0.001) in PITX2+/- deficient AF than in wild-type patients. In the clinical setting, the PITX2+/- genetic risk score did not affect the AF ablation rhythm outcome (Log-rank p=0.273). Conclusions: Consistent with previous clinical studies, the V-CPVI had effective anti-AF effects regardless of the PITX2 genotype, whereas V-AADs exhibited a more significant defragmentation or wave-dynamic change in the PITX2+/- deficient patients. Keywords: Atrial fibrillation, Computational modeling, PITX2, Dominant frequency, Antiarrhythmic drug